2014
DOI: 10.1186/2045-824x-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib significantly suppresses the proliferation, migration, apoptosis resistance, tumor angiogenesis and growth of triple-negative breast cancers but increases breast cancer stem cells

Abstract: The majority of triple-negative breast cancers (TNBCs) are basal-like breast cancers. However there is no reported study on anti-tumor effects of sunitinib in xenografts of basal-like TNBC (MDA-MB-468) cells. In the present study, MDA-MB-231, MDA-MB-468, MCF-7 cells were cultured using RPMI 1640 media with 10% FBS. Vascular endothelia growth factor (VEGF) protein levels were detected using ELISA (R & D Systams). MDA-MB-468 cells were exposed to sunitinib for 18 hours for measuring proliferation (3H-thymidine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 42 publications
4
46
1
Order By: Relevance
“…(Figure 2C). In contrast, sunitinib treated parental cells exhibited reduced migration (Figure 2C up-right panel), which is also observed in breast cancer cell lines (38). This could be the result of sunitinib-activated EMT signaling, which is dependent on either the activation of MET (35, 37) or AXL (21) that have been observed in other cancer cells.…”
Section: Resultsmentioning
confidence: 52%
“…(Figure 2C). In contrast, sunitinib treated parental cells exhibited reduced migration (Figure 2C up-right panel), which is also observed in breast cancer cell lines (38). This could be the result of sunitinib-activated EMT signaling, which is dependent on either the activation of MET (35, 37) or AXL (21) that have been observed in other cancer cells.…”
Section: Resultsmentioning
confidence: 52%
“…Notably, the increased resistance to tamoxifen, an anti-estrogen receptor-positive breast cancer drug, was accompanied by the selection of breast cancer cells with mammosphere-forming capacity (Raffo et al , 2013). Further, in mouse xenograft models of breast cancer, the tyrosine kinase inhibitor sunitinib was found to reduce tumor volume of triple-negative MDA-MB-468 cells but increased the frequency of breast cancer stem cells (Chinchar et al , 2014). Importantly, inhibitors of the metabolic pathway-associated mTOR were found to counteract tamoxifen-induced activation of breast cancer cells (Karthik et al , 2015), suggesting that resistance to temoxifen is associated with metabolic dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that secretome from FaDu-IRR and SCC-IRR cells increased HMEC-1 migration by ~2.6- and ~1.4-fold compared to secretome obtained from treatment-sensitive parental FaDu and SCC25 cells, respectively (Figure 9). Administration of currently existing anti-angiogenic compounds (anti-VEGF or anti-VEGF-R antibodies or small molecules) does not markedly improve the therapeutic response of primary or metastatic lesions, because despite effective suppression of angiogenesis these compounds can increase the number of intratumoral CSCs [35]. Hence, we believe that inhibiting Rac1 signaling in HNSCC cells with CSC properties could also contribute to the decrease of neoangio- and vasculogenesis.…”
Section: Introductionmentioning
confidence: 99%